Role of proinflammatory cytokines TNF-α (rs1800629) and IL-6 (rs1800795) in the pathogenesis of polycystic ovarian syndrome in North Indian females - Kaur, Parneet; Kaur, Khushpreet; Kaur, Rajinder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study aimed to determine whether TNF-α and IL-6 gene polymorphism, their epistatic effects and haplotypes confer pathogenesis of PCOS in north Indian females. Methods: A case-control study comprising DNA samples of 401 females (200 PCOS cases and 201 controls) of reproductive age. All the subjects were genotyped for TNF-α (-308 G/A) and IL-6 (-174 G/C) genes by tetra-primer ARMS PCR. Results: There were 41.5% PCOS females revealing hirsutism, 45.5% acne and 36% alopecia. High BMI (p=0.008) and W/H ratio (p=0.0001) was observed among PCOS cases. Frequency of minor allele A for -308 G/A TNF-α was significantly higher in PCOS cases than controls indicating 1.4 fold increased risk for PCOS (p=0.05, OR=1.41, 95% CI=1.00-1.99). -174 G/C IL-6 gene was in association with the decreased risk of PCOS. The epistatic effects of all the possible combinations of both the SNPs shows statistically significant differences (Interaction p value=0.014) indicating modulating effects of TNF-α and IL-6 polymorphism in response to PCOS. Haplotype HT3 AG (p=0.003, OR=2.22, 95% CI=1.31-3.78) was associated with increased risk of PCOS. Conclusions: The present findings suggest that TNF-α and IL-6 might contribute to pathogenesis of PCOS in north Indian females irrespective of a polymorphism of TNF-α (-308 G/A) and IL-6 (-174 G/C) genes.